2012
DOI: 10.4274/tftr.66588
|View full text |Cite
|
Sign up to set email alerts
|

Radikal Prostatektomi Sonrası Üriner İnkontinansın Düzelmesinde Pelvik Tabanda Biofeedback ve Elektrik Stimülasyonunun Etkisi

Abstract: Objective: Urinary incontinence (UI) is one of the most distressing postoperative problems of radical prostatectomy (RP) and negatively affects the quality of life (QOL). We assessed the effect of pelvic muscle exercises (PME), electrical stimulation (ES) and biofeedback (BFB) on UI after RP. Materials and Methods: 80 patients, who underwent RP, were randomized into three groups. Group I (n=26) received instructions about PME, group II (n=26) received ES and group III (n=28) received ES plus BFB. The treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In most of the analyzed research protocols, electrostimulation was combined with other PFM therapeutic techniques [ 16 , 27 , 30 , 33 , 40 , 48 , 52 ] and lasted between 15 [ 16 , 31 , 40 , 52 ] and 20 min [ 27 , 33 , 34 ]. Ahmed et al [ 16 ] observed that UI therapy outcomes may improve after combining ES therapy with BF [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In most of the analyzed research protocols, electrostimulation was combined with other PFM therapeutic techniques [ 16 , 27 , 30 , 33 , 40 , 48 , 52 ] and lasted between 15 [ 16 , 31 , 40 , 52 ] and 20 min [ 27 , 33 , 34 ]. Ahmed et al [ 16 ] observed that UI therapy outcomes may improve after combining ES therapy with BF [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…In most of the analyzed research protocols, electrostimulation was combined with other PFM therapeutic techniques [ 16 , 27 , 30 , 33 , 40 , 48 , 52 ] and lasted between 15 [ 16 , 31 , 40 , 52 ] and 20 min [ 27 , 33 , 34 ]. Ahmed et al [ 16 ] observed that UI therapy outcomes may improve after combining ES therapy with BF [ 16 ]. Mariotti et al [ 33 ] confirmed these findings in the early therapy of men after prostate surgery, with significant continence improvements appearing between the 4 week and 6 month follow-ups [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The additional benefits brought by ES on a basis of PFMT appeared conflicting owing to five positive results (Ahmed et al, 2012; Mariotti et al, 2009; Nakagawa et al, 2010; Soto Gonzalez et al, 2020; Yamanishi et al, 2010) and five negative results (Goode et al, 2011; Laurienzo et al, 2013, 2018; Moore et al, 1999; Wille et al, 2003). The main reason maybe the parameters of ES and site of stimulation differed greatly among the included studies.…”
Section: Discussionmentioning
confidence: 99%